Pemantauan Minum Obat dengan Menggunakan Media Komunikasi Digital pada Pasien Tuberculosis - Ristinawati Ristinawati; I Made Kariasa (Jurnal Keperawatan Silampari, 2022)
This study aims to explore the effectiveness of modifying drug-taking control using digital communication media on Tuberculosis survivors. The research method used is a literature review by searching five databases. Namely, Google Scholar, Clinical Key, EbscoHost, and Pubmed, using the keywords "Tuberculosis," "adherence," "internet", "Smartphone," and "Directly Observed." The results of the study found that the monitoring method for taking medication involved digital information technology, namely 1) a smartphone that can play videos and the "Video Observed Treatment" application can be installed, 2) "E monitor via a smartphone that is used as a reminder to take medication, 3) a device that functions as a monitoring box to remind people to take medication 4) Reminders that are carried out using telephone devices that are intervened directly from the center. In conclusion, patient adherence to treatment in the control group resulted in a lower estimate of the effectiveness of the intervention with the test case group using digital communication media. Keywords: Internet, Compliance, Drug Administration, Smartphone, Tuberculosis